New Insights on the Control and Function of Octopus Suckers. (5th February 2020) - Bagheri, Hosain; Hu, Anna; Cummings, Sheldon; Roy, Cayla; Casleton, Rachel; Wan, Ashley; Erjavic, Nicole; Berman, Spring; Peet, Matthew M.; Aukes, Daniel M.; He, Ximin; Pratt, Stephen C.; et al.
Abstract : Octopuses utilize their suckers for a myriad of functions such as chemo‐ and mechanosensing, exploring and manipulating objects, anchoring the body during crawling, and navigating through narrow passages. The sucker attachment mechanism grants the octopus the ability to perform many of these tasks. The goal of this study is to analyze sucker function and control through the assessment of pull‐off forces under different conditions. Sucker pull‐off forces are measured in Octopus bimaculoides (three females, seven males), when the arm is intact, amputated, and amputated with the suckers punctured. Greater sucker pull‐off forces are observed for amputated arms, plausibly indicating that the brain and/or the interbrachial commissure are responsible for triggering early sucker detachment in the intact animal. In addition, after piercing and compromising the sucker cavity, pull‐off force significantly decreases, indicating that the primary mechanism for sucker attachment is suction, and is less dependent on adhesion. These results provide new insights into the control and function of octopus suckers that can be integrated into the design and development of soft robot arms for aquatic applications. Abstract : The goal of this study is to explore octopus sucker function and control. In particular, it is discovered that the brain and/or interbrachial commissure are plausibly responsible for triggering early sucker detachment in the intact animal resulting in less pull‐off force, compared with that of amputated arms. Furthermore, the primary mechanism for sucker attachment is suction rather than adhesion.